2016
DOI: 10.1371/journal.pone.0147729
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Associations between Egg Consumption and Metabolic Syndrome in Adults ≥ 40 Years Old: The Yangpyeong Cohort of the Korean Genome and Epidemiology Study (KoGES_Yangpyeong)

Abstract: Since the 1970s, the public has been advised to limit egg consumption even though there is little evidence of any harmful effect of eggs on blood cholesterol. The purpose of this cross-sectional and prospective study was to evaluate the potential association between egg consumption and metabolic syndrome (MetS) and MetS components in adults ≥ 40 years in KoGES_Yangpyeong. Yangpyeong is a rural area in South Korea. A total of 2,887 subjects (men 1,115, women 1,772) were recruited from 2005 to 2009, based on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 36 publications
(43 reference statements)
3
27
0
Order By: Relevance
“…Likewise, a recent ecological study based on data obtained from 170 countries suggested, the consumption of meat contributes just as much as sugar to the growing burden obesity [37]. However, the contribution of frequent consumption of eggs for obesity is less studied and inconsistently observed [3840].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a recent ecological study based on data obtained from 170 countries suggested, the consumption of meat contributes just as much as sugar to the growing burden obesity [37]. However, the contribution of frequent consumption of eggs for obesity is less studied and inconsistently observed [3840].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Australian National Heart Foundation recommends a maximum intake of six eggs/week for both healthy individuals and those with T2DM 31 , whereas US guidelines have maintained a restriction on dietary cholesterol intake for diabetes patients, recommending that dietary cholesterol intake be limited to <300 mg/day (one egg contains about 200 mg of cholesterol) and <4 eggs/week 7 , 21 , 22 . The Korean Diabetes Association recommends a dietary cholesterol intake of <300 mg/day, which is identical to the dietary guideline for the general Korean population 9 . Our data support dietary cholesterol restrictions for Korean patients with T2DM but not for healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies might therefore not be suitable evidence for developing dietary guidelines for populations other than those of the US and the EU. There is limited information on the association between the level of egg consumption and the risk for cardiometabolic disease in the Korean population, whose average cholesterol intake is lower than that of Western populations 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a meta-analysis using 22 independent cohort studies, the association between higher egg consumption (≥1 egg/day) and the risk of CVD and cardiac mortality was not significant among non-diabetes patients [ 12 ]. In a Korean study of 2889 adults without chronic diseases, more than three eggs per week was significantly associated with a decreased risk of incidence for MetS in both men and women when compared to non-egg eaters [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies that reported null [ 10 , 21 ] or positive [ 4 ] association between egg intake and risk of type 2 diabetes or CVD, subjects with higher egg consumption were more likely to smoke, drink, and be less physically active. On the other hand, other studies found an inverse association between egg consumption and type 2 diabetes[ 7 ] or MetS [ 23 ], wherein subjects with high egg consumption were less likely to smoke or more physically active. While our study adjusted for such lifestyle factors, it is possible that the residual confounding effects of smoking, alcohol drinking, and of other unmeasured factors on the risk of MetS resulted in the observed gender difference.…”
Section: Discussionmentioning
confidence: 99%